2015
DOI: 10.1037/emo0000026
|View full text |Cite
|
Sign up to set email alerts
|

Patients respond more positively to physicians who focus on their ideal affect.

Abstract: Previous findings suggest that patients choose physicians whose affective focus matches how they ideally want to feel (Sims et al., 2014). For instance, the more people wanted to feel excitement, the more likely they were to hypothetically choose a new physician who promoted excitement. What remains unknown is whether this match shapes how patients actually respond to physicians after being assigned to them (i.e., whether they adhere to physicians’ recommendations more and evaluate physicians more positively).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 72 publications
4
31
2
1
Order By: Relevance
“…Second, they suggest that certain ideals (i.e., extreme happiness) may be detrimental to one’s health. In other research, we have also demonstrated how people’s ideal affect shapes their preferences for and evaluations of physicians, their adherence to physicians’ recommendations, and even their recall of physicians’ recommendations [22, 46, 47]. This work suggests that clinicians should also consider how patients’ ideal affect may influence how patients respond to them.…”
Section: The Roles Of Ideal Affect In Healthsupporting
confidence: 55%
See 1 more Smart Citation
“…Second, they suggest that certain ideals (i.e., extreme happiness) may be detrimental to one’s health. In other research, we have also demonstrated how people’s ideal affect shapes their preferences for and evaluations of physicians, their adherence to physicians’ recommendations, and even their recall of physicians’ recommendations [22, 46, 47]. This work suggests that clinicians should also consider how patients’ ideal affect may influence how patients respond to them.…”
Section: The Roles Of Ideal Affect In Healthsupporting
confidence: 55%
“…As mentioned above, in clinical settings, we have found that the more people value excited states, the more likely they are to choose but also to adhere to the recommendations of a physician who wants to help patients lead “dynamic” vs. “relaxed” lifestyles [47]. Indeed, compared to European Americans, Asian Americans respond less favorably to excitement vs. calm focused physicians: they are not only less likely to choose them, but also less likely to recall their recommendations and evaluate them positively [22].…”
Section: Implications For Applied Settingsmentioning
confidence: 99%
“…Consistent with Tsai et al, we found that should affect was unique from ideal affect. Although future research should examine the relation between state should affect and state ideal affect, we are confident in our findings; Sims and Tsai (2015) found positive associations between daily and trait ideal PA. Further, the CTL group differed from the clinical groups in should but not ideal affect. Finally, approximately 70% of the variance for should PA and NA was due to within-person variance.…”
Section: Discussionsupporting
confidence: 48%
“…Is it right?”). Indeed, across a variety of studies, we have observed only modest correlations between reports of actual affect and ideal affect (Sims, Tsai, Koopmann-Holm, Thomas, & Goldstein, 2014; Sims & Tsai, 2014; Tsai, 2007; Tsai, Knutson, & Fung, 2006; Tsai, Louie, Chen, & Uchida, 2007; Tsai, Miao, & Seppala, 2007; Tsai, Miao, Seppala, Fung, & Yeung, 2007), and structural equation modeling has revealed that actual affect and ideal affect are distinct constructs (Tsai, et al, 2006; Koopmann-Holm et al, 2014). …”
Section: Affect Valuation Theorymentioning
confidence: 85%
“…AVT also posits that while temperamental factors shape both ideal and actual affect, temperamental factors shape actual affect more than ideal affect (see Tsai, 2007). Across a variety of studies using different methods, we have gathered strong empirical support for these claims, and have shown that cultural differences in ideal affect produce cultural differences in consumer product preferences, conceptions of well-being, and evaluations of people (Sims & Tsai, 2014; Sims et al, 2014; Tsai, 2007; Tsai et al, 2006; Tsai, Louie, et al, 2007; Tsai, Miao, & Seppala, 2007; Tsai, Miao, Seppala, et al, 2007; Tsai, Chim, & Sims, in press). …”
Section: Affect Valuation Theorymentioning
confidence: 89%